Structural Explanations of Flavin Adenine Dinucleotide Binding in Drosophila melanogaster Cryptochrome. - Sjulstok, E.; Solov'yov, I.A. (The journal of physical chemistry letters, 2020)
Cryptochrome proteins are thought to be involved in light-sensitive magnetoreception in migratory birds triggered by flavin adenine dinucleotide (FAD) light absorption. A recent study, however, calls into question the ability of vertebrate cryptochrome proteins to bind FAD, rendering them unlikely to function as magnetoreceptive proteins. In this Letter, we investigate the structural changes occurring in Drosophila melanogaster cryptochrome, upon key amino acid mutations, which reduce FAD binding. Through computational analysis we have now suggested why some mutations do not preclude FAD binding in all vertebrate cryptochrome proteins.